A multidimensional data warehouse model for academic talent management - Sani, Iliyasu Muhammad
The notable growth in Malaysia ICT sector over the years and the dynamism in the global Information Technology ecosystem has created a huge demand for talents in the respective domain. Consequently, there are many Institute of Higher Learning (IHL) that offer ICT programs. However, mapping the right courses for industrial needs with the aim to strike a balance between supply and demand is not an easy task. This problem can be attributed to lack of centralized information about competent talents that will aid comprehensive analysis of current talents (undergraduate students). Next, there are no proper mapping between the talents and industrial needs in a single repository to provide information that will facilitate effective analysis between what we have (academic talents) and what we need to have (industrial needs). In order to solve the problem, this study proposes a model called Multidimensional Data Warehouse Model for Talent Management (TM). The idea is to integrate ICT Talent information based on academic performances from IHL and ICT Industrial needs into a single repository called the Talent Management Data Warehouse (TMDW). The aim is to provide reporting system to facilitate national pool of talents based on Students' Academic Performances (SAP) using available Business Intelligence (BI) technologies. Data for this study were obtained from an existing Academic System in Universiti Sultan Zainal Abidin (UniSZA) that has been integrated with the list of job vacancies from Multimedia Development Corporation (MDEC) Malaysia. For the purpose of tins study, data of students were obtained from Faculty of Informatics and Computing. Further, tile dimensional concepts within these data sets were identified; and the dimension and fact tables were generated. As a result, the star schema of the DW was created using multidimensional modeling techniques. Finally, formal Z-Specification has been used to validate the TMDW model. Several analytics reports were produced using Table Business Intelligence (BI) tool to ensure the effectiveness of the model. In conclusion, this study has demonstrated the feasibility of TMDW in improving ICT demand and supply process and in ensuring that both industrial and IHL gain benefit by integrating the information into a single repository.